EFEKTIVITAS STEINERNEMA SP. DALAM PENGENDALIAN HAMA SERANGGA TANAH PADA BERBAGAI TEKSTUR TANAH - SAFITRI, MERINA (Universitas Negeri Surabaya, 2013)
The land insect pests cause huge economic disadvantages because they caused damage on agricultural plants, hence agricultural production decreases. Therefore, one of biological control was done by Steinernema sp. This research aimed to determine the effectiveness of Steinernema sp. in controlling the soil insects pest in a variety of soil textures and get the most suitable texture of soil for applications of Steinernema sp. This was experimental research using Completely Randomized Design with 1 factor treatment, The soil land textures used were sand with porosity 56.98%; argillaceous sand with porosity 57.15%; clay with porosity 60.44%; clay with porosity 50.61%; and clay with porosity 35.64% with 4 repetitions. Data obtained were analyzed with ANOVA 1 way using programs SPSS 16.0 for windows. It can be concluded that there are differences in the effectiveness of Steinernema sp. in controlling soil insect pests at various land textures. The texture of the effective application of Steinernema sp. in controlling insect pests soil is sand with porosity 56.98%.